A Review of Colour Image Watermarking Scheme Based Image Normalized - Kaur, Ashminder; Lofty, (International Journal of Computer Sciences and Engineering, 2025)
Watermarking on Digital Images has dissimilar methods, some of them contracts with frequency domain. The Watermarking methods using frequency domain produce better results either concerns with image excellence or invisibility of the watermark. The numerical watermarking is such that it offers copyright protection by information hiding. The investigators all over the world are still trying to find out the way to create robust Digital Image Watermarking Methods. Digital image watermarking techniques have been developed widely in new years to maintain the broadcasting media and satisfied authentication, broadcast monitoring, copy control, and many other applications. The method involves introducing of the watermark in the host appearance in the Discrete Cosine Transform domain in a spread-spectrum format. The digital data are spread using the Internet. So digital data must be secure, copyright protected, and authenticated at the same time.